Pelatihan Penyusunan Pembukuan Keuangan dan Digital Marketing pada Usaha Banten Upakara Ibu Mangku Karta di Kota Denpasar - Putu Eny Suhardiyani; I Putu Widyarsana (Syntax Corporation Indonesia, 2025)
This community service program aims to enhance the partner's business management skills for ceremonial offerings through financial bookkeeping and digital marketing training. The methods include training on financial bookkeeping using the Paper.id application, designing business logos and banners, and digital marketing training via social media platforms such as Instagram and Facebook. The results indicate that the partner successfully understood and applied basic financial bookkeeping, designed business logos and banners, and utilized social media to expand market reach. This program effectively improved the partner's operational efficiency and business competitiveness.